Masculinidades e o Tribunal do Santo Ofício da Inquisição: a ação das visitações do Santo Ofício às capitanias do Norte da América portuguesa na defesa da Ordem Patriarcal séculos XVI e XVII - Cassio Bruno de Araujo Rocha (2014)
The dissertation consists on the study of the patterns of masculinities experienced and reifed by men and women entangled in the plots set up by the Inquisition in the Portuguese America between the second half of the XVI century and the second decade of the XVII. In order to accomplish this investigation, it resorted to the concepts of masculinity and hegemonic masculitiny that were set up by the anthropologist Raweyn Connell which plasticity enabled its operation for the analysis of practices performed by men in differents societies and cultures and of gender performativity, articulated by Judith Butler, which was displaced to the unsuspected context seeing how this field of investigation was articulated, inicially, to question gender relations in the contemporary western culture of the colonial and slave society that was consolidating itself in the period. Another important theoretical fundantion of the text is the model of power proposed (as diffuse, microscopic and proliferative) by Michel Foucault, which founds the taken on the Inquisitions actions, in this study, by the Visitations, as a mean to produce both men and women that experienced performativityly their genders accordingly to the cultural legitimate ideals, but also the deviant figures, specially the sodomites, both men and women (assimilated to the image of the heretic), which penalization was the source of the Inquisitions meaning and existence as a institution. The most important documents for the research are the confessions, denunciations and criminal litigation made to and by the visitators Heitor Furtado de Mendonça e Marcos Teixeira in their Visitations. The text examines cases revealing of different dimensions of masculinities and feminilities (under a relational perspective of gender) experienced by men and women in Portugals american colony; individuals used to a rustic way of life, divided between city and wilderness, but also full of pleasures, some of which suspicious to the Catholic churchs eyes, which was beginning to incorporate Trentos pastoral recomendations. Were selected reports made by men and women somehow envolved in crimes of blasfemy, fornication or its apology, witchcraft, sodomy (imperfect, perfect or feminine), bigamy and the defense of marital statuss superiority over the religiouss one.